System for Investigation of Friction Properties of the Road Surface - Janusz Pokorski; Andrzej Reński; Hubert Sar (The Baltic Journal of Road and Bridge Engineering, 2015)
Friction properties of the road surface have a great influence on the safety of automobile motion. These properties are characterized by the tyre-to-road adhesion coefficient, which is measured during the routine and acceptance investigations of roads. In the paper, the method of measurement of this coefficient is presented. For investigation of the tyre-to-road adhesion coefficient the special measurement system was developed. The main part of the system is dynamometer trailer, which makes it possible to measure the friction force between tyre and road surface. The adhesion coefficient as a quotient of the friction force and vertical load is a result of measurements. Additionally the system enables to determine the graph of the adhesion coefficient as a function of wheel slip ratio. In the paper a description of the measurement system and a principle of its operation are presented. Exemplary results of tyre-to-road adhesion coefficients measured on different roads are also presented. The results show many differences between these coefficients in dependence of road upper layer technology, degree of its wear, weather conditions, sliding velocity and others. The system originally designed for investigation of friction parameters of road surfaces can have much wider applications, for example in tyre investigations, for automotive experts, in the work of judgment witnesses and others.